Differential roles for MBD2 and MBD3 at methylated CpG islands, active promoters and binding to exon sequences - Günther, Katharina; Rust, Mareike; Leers, Joerg; Boettger, Thomas; Scharfe, Maren; Jarek, Michael; Bartkuhn, Marek; Renkawitz, Rainer; Justus Liebig University Giessen (My University, 2013)
The heterogeneous collection of nucleosome remodelling and deacetylation (NuRD) complexes can be grouped into the MBD2- or MBD3-containing complexes MBD2 NuRD and MBD3 NuRD. MBD2 is known to bind to methylated CpG sequences in vitro in contrast to MBD3. Although functional differences have been described, a direct comparison of MBD2 and MBD3 in respect to genome-wide binding and function has been lacking. Here, we show that MBD2 NuRD, in contrast to MBD3 NuRD, converts open chromatin with euchromatic histone modifications into tightly compacted chromatin with repressive histone marks. Genome-wide, a strong enrichment for MBD2 at methylated CpG sequences is found, whereas CpGs bound by MBD3 are devoid of methylation. MBD2-bound genes are generally lower expressed as compared with MBD3-bound genes. When depleting cells for MBD2, the MBD2-bound genes increase their activity, whereas MBD2 plus MBD3-bound genes reduce their activity. Most strikingly, MBD3 is enriched at active promoters, whereas MBD2 is bound at methylated promoters and enriched at exon sequences of active genes.
Keywords: ddc:570